Development of Nitrogen Recycling Strategies for Bioregenerative Life Support Systems in Space - Verbeelen, Tom; Leys, Natalie; Ganigué, Ramon; Mastroleo, Felice (Frontiers in Microbiology, 2021)
To enable long-distance space travel, the development of a highly efficient and robust system to recover nutrients from waste streams is imperative. The inability of the current physicochemical-based Environmental Control and Life Support System (ECLSS) on the ISS to produce food in situ and to recover water and oxygen at high enough efficiencies results in the need for frequent resupply missions from Earth. Therefore, alternative strategies like biologically-based technologies called Bioregenerative Life Support Systems (BLSSs) are in development. These systems aim to combine biological and physicochemical processes, which enable in situ water, oxygen and food production (through the highly efficient recovery of minerals from waste streams). Hence minimalizing the need for external consumables. One of the BLSS initiatives is the European Space Agency’s (ESA) Micro-Ecological Life Support System Alternative (MELiSSA). It has been designed as a 5-compartment bioengineered system able to produce fresh food and oxygen and to recycle water. As such, it could sustain the needs of a human crew for long-term space exploration missions. A prerequisite for the self-sufficient nature of MELiSSA is the highly efficient recovery of valuable minerals from waste streams. The produced nutrients can be used as a fertilizer for food production. In this review, we discuss the need to shift from the ECLSS to a BLSS, provide a summary of past and current BLSS programs and their unique approaches to nitrogen recovery and processing of urine waste streams. In addition, compartment III of the MELiSSA loop, which is responsible for nitrogen recovery, is reviewed in-depth. Finally, past, current and future related ground and space demonstration and the space-related challenges for this technology are considered.